Mycotoxin production by Aspergillus niger aggregate strains isolated from harvested maize in three Portuguese regions - Soares, Célia Maria Gonçalves (2013)
Background: Maize is considered one of the crops more susceptible to mycotoxins in the world. Two of the mycotoxins commonly associated with maize are fumonisins and ochratoxin A. Aspergillus niger is a known producer of ochratoxin A and is easily found in maize. Recently, however, Aspergillus niger has been reported to produce as well fumonisins, mainly fumonisin B2. Aims: The aim of this study was to isolate Aspergillus niger strains from maize samples collected in three Portuguese maize growing regions and to detect the production of both fumonisin B2 and ochratoxin A. Methods: In order to do this, 95 maize samples were collected, plated and all observable Aspergillus section Nigri strains were isolated. Strains were morphologically characterized and mycotoxin production was determined by HPLC-FD. Results: Isolations resulted in a total of 270 strains of black Aspergillus from 73 samples (77% of the samples). About 14% of those strains were found to produce ochratoxin A and 39% of the strains were found to produce fumonisin B2. Conclusions: An association between the production of these two mycotoxins could not be found and no conclusions could be taken whether the presence of Aspergillus niger aggregate strains will increase the risk of maize contamination with fumonisins and more specifically with fumonisin B2.